ОСОБЛИВОСТІ ФОРМ ГУМАНІСТИЧНОЇ ДОПОМОГИ УЧНЯМ ШКІЛ-ІНТЕРНАТІВ У ПРОЦЕСІ ЇХ САМОВИЗНАЧЕННЯ (Педагогіка вищої та середньої школи, 2022)
The question is specificity of the humanistic help the pupil of schools - boarding schools (in particular to schoolboys with natural the slowed down rate of intellectual development), directed on liquidation of blanks in knowledge, skills of such children, their correction negative behavior, increase of a level o f their adaptation in existing vital conditions o f schools - boarding schools and to a social environment.